2001
DOI: 10.1093/brain/124.5.893
|View full text |Cite
|
Sign up to set email alerts
|

Anti-GQ1b ganglioside antibodies mediate complement-dependent destruction of the motor nerve terminal

Abstract: Miller-Fisher syndrome is an autoimmune neuropathy characterized by ataxia, areflexia and ophthalmoplegia, and in the majority of cases the presence of high titres of anti-GQ1b ganglioside antibodies. In an ex vivo model, human and mouse anti-GQ1b antibodies have been shown previously to induce a complement-dependent alpha-latrotoxin-like effect on the murine motor endplate, i.e. they bring about massive quantal release of acetylcholine and eventually block neuromuscular transmission. Using immunofluorescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
114
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(124 citation statements)
references
References 54 publications
9
114
1
Order By: Relevance
“…The neuromuscular junction (NMJ) is rich in gangliosides, lies outside the blood-nerve barrier, and is an important site of antibody-mediated autoimmune diseases (61). In vitro electrophysiological evidence suggests muscle weakness may be affected via the action of antibodies on the NMJ (14).…”
Section: Animal Models and Ganglioside Mimicry Affecting Function Ofmentioning
confidence: 99%
“…The neuromuscular junction (NMJ) is rich in gangliosides, lies outside the blood-nerve barrier, and is an important site of antibody-mediated autoimmune diseases (61). In vitro electrophysiological evidence suggests muscle weakness may be affected via the action of antibodies on the NMJ (14).…”
Section: Animal Models and Ganglioside Mimicry Affecting Function Ofmentioning
confidence: 99%
“…2) Deposits of activated complement factors, C3d and C5b-9, are present on the outer membrane of Schwann cells in acute inflammatory demyelinating polyneuropathy (5), and on the axolemma of motor fibers in acute motor axonal neuropathy (6). 3) In the mouse diaphragm-phrenic nerve model, complement activation is crucial for the induction of the Ab-mediated pathophysiological effects and for axonal cytoskeletal breakdown and perisynaptic Schwann cell damage (7)(8)(9). The complement dependency of the pathogenic effect of anti-ganglioside Abs was confirmed in an in vitro assay using neuronal cells expressing gangliosides (10).…”
Section: G Uillain-barré Syndrome (Gbs)mentioning
confidence: 99%
“…Gangliosides can also function as cell surface receptors for microbial toxins (Fishman, 1982;Bullens et al, 2002). Experimental studies in mice by us and others have shown that GBS/MFS-associated anti-ganglioside antibodies can mediate functional and structural damage to neuromuscular junctions (NMJs) (Buchwald et al, 1995;Plomp et al, 1999;Ortiz et al, 2001;O'Hanlon et al, 2001;Halstead et al, 2004;Santafe et al, 2005).…”
Section: Introductionmentioning
confidence: 99%